Dying as a Macedonian: From Aigai to Shatby (Bulletin de la Société Archéologique d’Alexandrie, 2025)
The paper discusses the Hellenistic necropoleis of Alexandria in Egypt: the tombs, the finds, the paintings, Greco-Egyptian ideas on death and dying. We will be exploring Macedonian responses to death and dying, as well as the ways Macedonian mortuary habits were transmitted, transposed, developed and “edited”, once the Macedonians found themselves on top of the world, and in lands so different from their own. From Macedon to Asia and Egypt, and from Aigai and Mieza to Shatby, Macedonians had to renegotiate their fundamental beliefs on death and the afterlife, committing themselves to the amalgam we now understand as “Ptolemaic Alexandria”.